2019
DOI: 10.1038/s41598-019-39172-8
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic changes in spontaneous cardiovagal baroreflex sensitivity during passive hyperthermia

Abstract: Successful adaptation to passive hyperthermia requires continual adjustment of circulation, which is mediated mainly by the autonomic nervous system. The goal of this study was to explore the alterations in spontaneous cardiovagal baroreflex sensitivity (BRS) during exposure to a hot environment. To continuously follow changes in core body temperature (Tc), haemodynamics, and BRS, male Wistar-Kyoto rats were implanted with telemetric transmitters. BRS at an ambient temperature of 23 °C was not steady but oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…0.3–0.8°C; Lee et al., 2003; Pecanha et al., 2017; Yamazaki & Sone, 2000, 2001), and while this is not always the case (i.e. 1.3°C increase; Yamazaki et al., 1997), rodent research has demonstrated non‐linear changes in cBRS with heat stress (Turcani & Ghadhanfar, 2019). These findings indicate that there may be temperature‐dependent changes in cardiac autonomic modulation, but further research is required to determine dose–response relations.…”
Section: Discussion and Practical Recommendationsmentioning
confidence: 99%
“…0.3–0.8°C; Lee et al., 2003; Pecanha et al., 2017; Yamazaki & Sone, 2000, 2001), and while this is not always the case (i.e. 1.3°C increase; Yamazaki et al., 1997), rodent research has demonstrated non‐linear changes in cBRS with heat stress (Turcani & Ghadhanfar, 2019). These findings indicate that there may be temperature‐dependent changes in cardiac autonomic modulation, but further research is required to determine dose–response relations.…”
Section: Discussion and Practical Recommendationsmentioning
confidence: 99%